Polish Experience in the Search for the Optimal Model of Performing and Financing Metropolitan Tasks - Ofiarska, Małgorzata (Public Governance, Administration and Finances Law Review, 2023)
For nearly 25 years, the problem of managing public affairs in metropolitan areas in Poland has been present in the public debate and the legislative process. The aim of the study is to analyse and evaluate the projects and adopted acts dedicated to such areas. Using legal dogmatics and historical and legal methods, successive attempts have been made to adopt a legal basis for managing metropolitan areas and performing and financing metropolitan tasks, both in the form of a single act, regulating the organisation and functioning of metropolitan selfgovernment throughout the country using a comprehensive and framework approach and legal solutions dedicated to only one metropolitan area. In 2017, the first and so far the only metropolitan union in Poland was established in the Silesian Voivodeship. It was determined that the search for appropriate organisational forms for the performance and sources of financing metropolitan tasks had not yet been completed. So far, an agreement has been reached on the choice of a statutory functional solution based on the structure of a metropolitan union and a catalogue of metropolitan tasks, separate from the public tasks of municipalities and districts. The metropolitan union was provided with financing from the state budget.